Study on the Methods for Generating Optical PAM-4 Signal With the Standard Silicon Mach–Zehnder Optical Modulator - Sizhu Shao; Jianfeng Ding; Lingchen Zheng; Lei Zhang; Xin Fu; Xuezhe Zheng; Lin Yang (IEEE Photonics Journal)
We propose an analytical model to evaluate three different methods for generating the optical four-level pulse-amplitude-modulation (PAM-4) signal with a standard silicon Mach–Zehnder (M–Z) optical modulator. With this model, we further use the uniformity of the modulation intervals as the metric to find the optimum operating points to achieve optical PAM-4 signals with uniform intervals for all three methods. We find that to achieve a uniform optical PAM-4 signal, the operating point for the single-arm-driving configuration needs to be farther away from the quadrature point compared with the other driving configurations. We characterize the optical PAM-4 signals generated by the three methods and verify the theoretical analysis using a fabricated 39.2 GHz silicon M–Z optical modulator. A 50 Gbaud optical PAM-4 modulation with open eye is successfully demonstrated using the silicon modulator.